Визначення критеріїв для вибору інформаційної системи управління проєктом - Купенко, М. І. (ХНУРЕ, 2024)
In the modern business landscape, the selection of a Project Management Information System (PMIS) emerges as an exceedingly critical undertaking for enterprises seeking to maintain competitiveness and efficiency. This article delves deep into the process of choosing criteria for the selection of a PMIS, encompassing a comprehensive analysis of functionality, cost considerations, adaptation duration, and the accessibility of final documentation crucial for managerial personnel. All of the criteria are explained and analyzed. Considered their importance and necessity when choosing PMIS.
Keywords: Project Management Information System (PMIS)